Clinical Overview of Leber Hereditary Optic Neuropathy - Stramkauskaitė, Almina; Povilaityte, Ieva; Glebauskiene, Brigita; Liutkeviciene, Rasa (Acta medica Lituanica, 2022)
Leber hereditary ptic neuropathy (LHON) is a disease of young adults with bilateral, painless, subacute visual loss. The peak age of onset of LHON is in the second and third decades of life. Men are 4 times more likely to be affected than women. In about 25-50% of cases, both eyes are affected simultaneously. In unilateral cases, the other eye is usually affected 2 to 3 months later. Visual acuity deteriorates to counting fingers or worse with a dense central or centrocecal scotoma. In the subacute phase, the optic disc may appear hyperemic with swelling of the peripapillary retinal nerve fibre layer, peripapillary telangiectasias, and increased vascular tortuosity. Ocular coherence tomography of the macula shows marked thinning of the ganglion cell complex even at this stage. The diagnosis of LHON is made in a subject with a consistent clinical history and/or one of three common pathogenic mitochondrial DNA (mtDNA) variants identified by molecular genetic testing. Idebenone was approved by the European Medicines Agency under exceptional circumstances for the treatment of LHON. Current evidence suggests some benefit to vision in a subset of affected individuals treated with idebenone, particularly when treated within the first year of onset of vision loss. In this article, we discuss aetiology, clinical features, diagnosis, differential dignosis, prognosis and treatment.